2019
DOI: 10.3390/nano9040623
|View full text |Cite
|
Sign up to set email alerts
|

Control of Nitrogen Inhomogeneities in Type-I and Type-II GaAsSbN Superlattices for Solar Cell Devices

Abstract: Superlattice structures (SLs) with type-II (GaAsSb/GaAsN) and -I (GaAsSbN/GaAs) band alignments have received a great deal of attention for multijunction solar cell (MJSC) applications, as they present a strongly intensified luminescence and a significant external quantum efficiency (EQE), with respect to the GaAsSbN bulk layers. Despite the difficulties in characterizing the distribution of N in dilute III-V nitride alloys, in this work we have obtained N-compositional mappings before and after rapid thermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The GaAsN signal located on the right side is asymmetrically broadened which might suggest inhomogeneous nitrogen distribution in GaAsN layer. Composition fluctuations in dilute nitride layers such as GaAsN or InGaAsN are well known [16,[50][51][52]. Nitrogen has a tendency to form clusters, which, together with N-related defects (for instance, (N-N) As , (N-As) As [5,35]), contribute to the formation of non-radiative recombination centers [30] and carrier localization effects [53].…”
Section: Structural Characterizationmentioning
confidence: 99%
“…The GaAsN signal located on the right side is asymmetrically broadened which might suggest inhomogeneous nitrogen distribution in GaAsN layer. Composition fluctuations in dilute nitride layers such as GaAsN or InGaAsN are well known [16,[50][51][52]. Nitrogen has a tendency to form clusters, which, together with N-related defects (for instance, (N-N) As , (N-As) As [5,35]), contribute to the formation of non-radiative recombination centers [30] and carrier localization effects [53].…”
Section: Structural Characterizationmentioning
confidence: 99%
“…Recently, type II GaAsSb/GaAsN superlattices (SLs) have been proposed as a suitable structure to form such a 1.0-1.15 eV sub-cell, that would allow their implementation in the optimal design of GaAs lattice-matched multijunction solar cells [4,5]. Here, the authors suggest that this strategy optimizes control over the composition distribution of the different elements concerning bulk GaAsSbN counterparts, reducing the growing problems associated with concomitant Sb and N incorporation [6,7]. However, atomic-scale compositional analyses by electron microscopy in this type of SLs revealed that while the N distribution is spatially confined in the GaAsN layers, the same is not true for that of GaAsSb layers, there is a significant Sb segregation affecting both interfaces [8].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in the quaternary GaAs 1-x-y Sb x N y regions, the simultaneous presence of Sb also hinders the N characterization [177]. However, a new methodology proposed in [177,178] to detect and quantify N presence through ADF imaging has been employed on some samples of this Thesis. The scattered intensity in HAADF conditions is especially sensitive to high Z-number atoms (which is known as Z-contrast) [179].…”
Section: Tem Stemmentioning
confidence: 99%